Acute on chronic liver failure in non-alcoholic fatty liver and alcohol associated liver disease - Singal, Ashwani K. (Transl Gastroenterol Hepatol, 2019)
Acute on chronic liver failure (ACLF) presents acutely with multiple organ failure and is precipitated by an acute event. The syndrome has high short-term mortality with a potential of returning to baseline liver function if the precipitating event is controlled and patient/s survive the acute event. With heterogeneous definition across the globe of this syndrome, there is a clinical unmet need to homogenize this definition as basis for developing pathogenesis targets, collaboration across countries and centers, and identifying new therapeutic targets. Although, the syndrome can occur in any chronic liver disease with or without cirrhosis, the increasing prevalence of nonalcoholic fatty liver disease (NAFLD) and alcohol associated liver disease (AALD) all across the world, this review will discuss specific issues regarding ACLF among patients with chronic liver disease from NAFLD and ALD.